The People's Rights, 1910 - Churchill, Winston S. (Early Speeches., 2013)
This inspiring collection of campaign speeches from the WWII-era British Prime Minister brings the great politician's work to life. Legendary politician and military strategist Sir Winston Churchill was a master not only of the battlefield, but of the page and the podium. Over the course of forty books and countless speeches, broadcasts, news items and more, he addressed a country at war and at peace, thrilling with victory but uneasy with its shifting role in global politics. In 1953, he was awarded the Nobel Prize for Literature for "his mastery of historical and biographical description as well as for brilliant oratory in defending exalted human values." During his lifetime, he enthralled readers and brought crowds roaring to their feet; in the years since his death, his masterful writing has inspired generations of eager history buffs. In 1904, Sir Winston Churchill crossed a gaping political divide to join the Liberal Party. Conservatives saw him as a traitor to his former political party; liberals, as a strong champion for progressive views. This comprehensive collection was originally published in 1909, as part of Churchill's campaign efforts to support a Liberal budget rejected by the House of Lords. It contains his impassioned speeches delivered during a nine-day campaign, offering scathing criticism of the House of Lords' decision and supporting causes such as free trade. Ultimately, Churchill's efforts contributed to a Liberal majority and successful budget passage. It offers the modern reader a revealing glimpse into a pivotal moment in Britain's political history.